Does region of origin influence the timing and outcome of first‐line antiretroviral therapy in France?. Issue 2 (3rd December 2018) - Gatey, C; Brun, A; Hamet, G; Diamantis, S; Sellier, P; Bouchaud, O; Garrait, V; Rozenbaum, W; Molina, JM; Abgrall, S; ,
Abstract : Objectives: The aim of the study was to assess whether the timing of combination antiretroviral therapy (cART) initiation, the choice of cART and virological response differ in migrants versus European natives in the north and east of Paris area, after dissemination of French recommendations for universal treatment. Methods: Antiretroviral therapy‐naïve HIV‐1‐infected adults with at least two follow‐up visits at one of 15 participating centres between 1 January 2014 and 31 March 2015 were included in the study. Factors associated with cART initiation before 31 March 2015, with protease inhibitor (PI)‐containing cART among individuals initiating cART, and with 1‐year virological success after cART initiation were assessed using multivariable logistic regression models. Sex, age, region of origin [Western Europe, sub‐Saharan Africa (SSA) or other], HIV transmission group, baseline AIDS status, CD4 cell count and plasma viral load (VL), and hepatitis B and/or C virus infection were considered in the analyses. Results: Among 912 individuals, only 584 (64%) started cART during the study period. After adjustment, migrants from SSA were half as likely to initiate cART and to have a subsequent virological response compared with individuals from Western Europe [adjusted odds ratio (aOR) 0.54; 95% confidence interval (CI) 0.36–0.82; and aOR 0.52; 95% CI 0.28–0.98, respectively]. PI‐containing cART was more frequently prescribed in migrants from SSA, in people with lower CD4 cell counts and in people with higher VL. Conclusions: Even in the context of universal cART recommendations and of free access to care, migrants from SSA still have delayed access to cART and a lower virological response. Efforts are still necessary to provide immediate cART to all people living with HIV.